An Analysis of the Spatial Characteristics of Jin Ancestral Temple Based on Space Syntax - Chuanjin Hu; Yuanbo Qi; Chongen Wang (Buildings)
As a model of ancient Chinese architecture, Jin Ancestral Temple’s spatial layout and functional hierarchy reflect its profound cultural connotations and historical evolution. This paper systematically studies Jin Ancestral Temple from the perspectives of spatial relationships, visibility, and accessibility based on space syntax and visual graphics analysis methods. Through the construction and analysis of spatial relationship diagrams and topological diagrams, this study quantitatively identifies key differences in spatial depth and integration along the central axis of Jin Ancestral Temple. The sacrificial buildings, such as Uonuma Flying Beam and the Sacrificial Temple, exhibit high spatial depth and low integration, reflecting their secluded nature, which enhances the solemnity and focus of ritual activities. In contrast, landscape buildings like Jinren Terrace, with their low spatial depth and high integration, function as open spaces that facilitate movement and act as pivotal points in the visitor circulation network. Visual Graph Analysis (VGA) shows that the central axis area has the unique characteristics of a “visual center” and a “transportation hub”. The plaza on the north side of the reflecting pool forms the core area of visual connectivity, while Jinren Terrace becomes the transportation node with the highest accessibility. This design of “separation and connection” combines visual guidance with traffic flow, providing a layered spatial experience that stimulates visitors’ interest in exploration. Meanwhile, the historical development of Jin Ancestral Temple shows a clear trend of “growth”. From its early single function of worship, it gradually expanded into a complex architectural complex integrating worship, landscape, and belief, reflecting the changes in social, political, and cultural needs in different periods. The research results not only demonstrate the high degree of balance between the functionality and ornamental value of Jin Ancestral Temple’s buildings, but also reveal their unique value as cultural heritage in terms of spatial layout and aesthetic design. This paper provides a scientific basis for the protection and tourism development of Jin Ancestral Temple, and offers a new perspective on the combination of traditional architectural research and spatial analysis methods.